2019
DOI: 10.1590/0037-8682-0302-2019
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E seroprevalence and associated risk factors in Croatian liver transplant recipients

Abstract: Introduction: Solid-organ transplant recipients are at risk of hepatitis E virus (HEV) infection. We analyzed the seroprevalence/ risk factors of HEV in Croatian liver transplant recipients. Methods: Two hundred forty-two serum samples were tested for HEV immunoglobuline IgG/IgM and HEV RNA. Sociodemographic data and risk factors were collected using a questionnaire. Results: HEV IgG seroprevalence rate was 24.4%. Positive/equivocal HEV IgM were found in two patients. HEV RNA was not detected. Logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…The percentage of male LT recipients in the cohorts ranged from 51.2% to 83.3% 9,10,13–19,21,23,24 . At the time of evaluation (ranging from 3 to 107 months post‐LT) 9,10,15,16,19,21,23,24 the mean/median values of AST, ALT and bilirubin were from 24 to 59 IU/L, 10,15,16,24 19 to 71 IU/L 10,11,13,15,16,24 and 4 to 36 μmol/L, 10,11,15,16,24 respectively. Based on the available data, 34 of the 5227 LT recipients tested for HEV RNA had confirmed HEV infection at 5.5 to 96 months post‐LT 10,15,16,18,20,21 having mean/median AST, ALT and bilirubin levels from 29.5 to 250 IU/L, 15,16,18 22.8 to 250 IU/L 15,16,18,20,24 and 10.3 to 198 μmol/L, 15,16,18,20 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of male LT recipients in the cohorts ranged from 51.2% to 83.3% 9,10,13–19,21,23,24 . At the time of evaluation (ranging from 3 to 107 months post‐LT) 9,10,15,16,19,21,23,24 the mean/median values of AST, ALT and bilirubin were from 24 to 59 IU/L, 10,15,16,24 19 to 71 IU/L 10,11,13,15,16,24 and 4 to 36 μmol/L, 10,11,15,16,24 respectively. Based on the available data, 34 of the 5227 LT recipients tested for HEV RNA had confirmed HEV infection at 5.5 to 96 months post‐LT 10,15,16,18,20,21 having mean/median AST, ALT and bilirubin levels from 29.5 to 250 IU/L, 15,16,18 22.8 to 250 IU/L 15,16,18,20,24 and 10.3 to 198 μmol/L, 15,16,18,20 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among the six studies published between 2009 and 2014, 9–14 only three evaluated HEV RNA (with 9,10 or without 12 HEV Abs) including 820 (53%) recipients. In contrast, all the studies published between 2015 and 2020, 15–24 evaluated HEV RNA (with 16,17,19,23,24 or without HEV Abs 15,18,20–22 ). The seroprevalence of anti‐HEV IgG ranged from 3.16% to 27.7% and 2.9% to 53.3% (24.4% in the only European cohort reporting IgG) between 2009 and 2014 and between 2015 and 2020, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[23] In the study by Kamar et al [13] in 2008, HEV seroprevalence was 14.5% and 10.4% in kidney and liver transplant recipients, respectively. The study by Mrzljak et al [24] in Croatia showed that the HEV seroprevalence was 24.4% in liver transplant patients. In a study by Buffaz et al [25] in France, anti-HEV IgG antibody positivity was identified in 28% of the liver transplant recipients tested.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some studies, no significant relationship was found between drinking water source and anti-HEV IgG antibody positivity. [8,24] The risk of HEV seropositivity being higher in a living-donor liver transplant recipients is difficult to explain, but this could be because 14 (63.6%) of 21 living-donor recipients were born in Eastern and Southeastern Anatolia, where HEV is quite common.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one study addressed the HEV seroprevalence in the Croatian transplant recipients [59]. In 2017, a cross-sectional study conducted in a cohort of 242 adult liver transplant recipients, transplanted from 1994 to 2013 in a single high-volume liver transplant center, showed an HEV IgG seroprevalence rate of 24.4%.…”
Section: Hepatitis E Virus In Croatia-human Studiesmentioning
confidence: 99%